Structural change in the brazilian economy in the 2000s - Alexandre Messa (Revista de Economia Contemporânea, 2013)
This paper investigates the sources of structural change in the Brazilian economy in the 2000s. On that purpose, it uses the input-output structural decomposition analysis and introduces a method to correct the influence of prices on the time behavior of the technical coefficients, making them actually represent changes in the production structure. Results show that most of the growth differential between services and industry in that period was induced by the production structure: more precisely, by a lower intermediate consumption of domestic industrial inputs by the production chain of all economic sectors, concomitant with a higher intermediate consumption of services.